Analisis Framing Pemberitaan Naturalisasi Pemain Tim Nasional Indonesia pada Media Republika Online dan Kompas.com - Afifullah, Muhammad; Qadzafi, Syafawi Ahmad; Fathan, Fathan (UIN Raden Mas Said Surakarta, 2024)
This research examines how Republika Online and Kompas.com frame the naturalized players of the Indonesian national team through text analysis. The phenomenon of player naturalization has become a controversial issue in Indonesian society along with PSSI's policy of massively recruiting players of Indonesian descent to strengthen the national team. This research employs a qualitative approach using the Zhongdang Pan & Gerald M. Kosicki framing analysis model. The study reveals that both Republika Online and Kompas.com frame the coverage of Indonesian national team's naturalized players positively. However, the difference lies in Republika Online's use of assertive editorial content, while Kompas.com reports the momentum comprehensively and straightforwardly, without using the editorial term